THE APPLICATION OF HEMP-BASED PREPARATIONS IN ONCOLOGY PATIENTS - Kladar, Nebojša; Bjelić, Katarina (Archives of Pharmacy, 2023)
The use of hemp (Cannabis sativa L., Cannabaceae) for therapeutic purposes has been known since ancient times. Regarding palliative care and treatment of cancer patients, the hemp is gaining scientific interest in the seventies of the last century. So far, more than 400 biologically active compounds have been isolated from hemp, while the most studied ones are cannabidiol (CBD), as the main non-psychoactive and Δ9-tetrahydrocannabiol (Δ9-THC), as the main psychoactive compound. Numerous preclinical studies have highlighted phytocannabinoids as potential agents for treatment of various organs cacinoma, such as lungs, stomach, colon and leukemia. However, due to insufficient clinical data on the effectiveness of these substances, they are not the drugs of choice in most cases. Clinical studies have been conducted only for some types of tumors, such as recurrent glioblastoma resistant to chemo- and radiotherapy. Administration of Δ9-THC in these patients only in some cases led to improvement of symptoms, and in most cases the condition remained the same or even worsened (1). The application of cannabinoids is of the greatest importance in the symptomatic treatment of oncology patients. The synthetic cannabinoid nabilone has been shown to be effective in suppressing nausea and vomiting, as well as increasing appetite in chemotherapy patients (2). Cannabinoids have shown the potential for a wide range of pharmacological activities in preclinical studies, however, insufficient clinical data limit their use. It is necessary to conduct more research in order for these compounds to find adequate place in the therapy of oncology patients.